2006
DOI: 10.1158/0008-5472.can-05-4605
|View full text |Cite
|
Sign up to set email alerts
|

Death Receptor-3, a New E-Selectin Counter-Receptor that Confers Migration and Survival Advantages to Colon Carcinoma Cells by Triggering p38 and ERK MAPK Activation

Abstract: E-selectin-mediated adhesion of colon cancer cells to endothelial cells is a key event in metastasis. However, the signaling mechanisms that confer metastatic advantages to cancer cells adhering to E-selectin are ill defined. By using affinity column chromatography and pull-down assays on purified membrane extracts of HT29 and LoVo cells coupled to mass spectrometry analysis, we obtained the first evidence indicating that E-selectin binds to death receptor-3 (DR3) expressed by the cancer cells. Thereafter, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
95
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(98 citation statements)
references
References 46 publications
2
95
0
1
Order By: Relevance
“…Rat Neu2 also decreased sialyl-Le x in mouse colon 26 cells (28), whereas human NEU2 is almost absent in colon mucosa. DR3 glycoproteins of the death receptor family may include sialyl-Le a and sialyl-Le x , and could bind to E-selectin in HT29 and Lovo cells (39), impacting on cell motility and cell survival. As our previous study (19) showed that NEU4S enhanced TRAIL-induced apoptosis in colon cancer cells, it is conceivable that it desialylates the sialyl Lewis antigens on DR3 glycoproteins, thus reducing their binding to E-selectin and inhibiting cell motility and survival.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rat Neu2 also decreased sialyl-Le x in mouse colon 26 cells (28), whereas human NEU2 is almost absent in colon mucosa. DR3 glycoproteins of the death receptor family may include sialyl-Le a and sialyl-Le x , and could bind to E-selectin in HT29 and Lovo cells (39), impacting on cell motility and cell survival. As our previous study (19) showed that NEU4S enhanced TRAIL-induced apoptosis in colon cancer cells, it is conceivable that it desialylates the sialyl Lewis antigens on DR3 glycoproteins, thus reducing their binding to E-selectin and inhibiting cell motility and survival.…”
Section: Discussionmentioning
confidence: 99%
“…Pathway-Previous observations have showed that sialyl-Le a and sialyl-Le x regulate cell motility (39). To test whether NEU4 affects cell migration through desialyla- Homogenates from HEK293T cells transfected with the respective sialidase cDNAs were used as enzyme sources, and essentially equal amounts for each sialidase were applied.…”
Section: Neu4s Suppresses E-selectin-induced Cell Motility Through Acmentioning
confidence: 99%
See 1 more Smart Citation
“…14 In cancer cells, p38a/b are required for breast and colorectal cancer cell migration and metastasis formation in mice. 15,16 However, over-activation of p38 by a constitutively active form of its upstream kinase (MKK6EE) eliminates the tumor-prone phenotype of mice obtained by intercrossing transgenic mice with breast-restricted expression of Wip1, the p53-induced phosphatase targeting p38 and the oncogene ErbB2. 17 Moreover, p38a/b contribute to TGFb-dependent tumor progression by inducing epithelial to mesenchymal transdifferentiation and cell migration, 18 and to rat chondrosarcoma cell proliferation.…”
mentioning
confidence: 99%
“…however, a recent study showed that dr3 may be a new receptor for E-selectin, which has been linked with cancer metastasis. The findings of this study indicate that the activation of dr3 in response to E-selectin triggers the transendothelial migration of cancer cells and protects them against apoptosis, suggesting that dr3 has evolved to provide metastatic advantages to colon cancer cells (13).…”
Section: Introductionmentioning
confidence: 76%